Whole exome sequencing identified a novel missense alteration in CC2D2A causing Joubert syndrome 9 in a Pakhtun family. (27th October 2020) - Khan, Muhammad Ismail; Latif, Muhammad; Saif, Maria; Ahmad, Hilal; Khan, Atta Ullah; Naseer, Muhammad Imran; Hussain, Hafiz Muhammad Jafar; Jelani, Musharraf
Abstract: Background: Joubert syndrome (JBTS) is a heterogenous disorder characterized by intellectual disability, developmental delays, molar tooth sign in brain imaging, hypotonia, ocular motor apraxia and overlapping features of ciliopathies. There are 36 clinical subtypes of JBTS, with an equal number of genes known so far for this phenotype. Methods: Whole exome sequencing (WES) and Sanger sequencing were performed for the molecular diagnosis of a Pakhtun family affected with Joubert syndrome type 9 (JBTS9). Results: A novel homozygous missense variant (c.4417C>G; Pro1473Ala) in exon 34 was identified in coiled‐coil and C2 domains‐containing the protein 2A ( CC2D2A ; NM_001080522) gene. The variant co‐segregated in autosomal recessive fashion within the family and was not found in 200 ethnically matched unaffected individuals. In silico analyses supported the pathogenic effect of the altered CC2D2A protein. Conclusions: To the best of our knowledge, this is the first report of CC2D2A alteration co‐segragating with a JBTS9 phenotype in a Pakhtun family from Pakistan. Our findings broaden the pathogenic spectrum of JBTS9, adding a novel variant to CC2D2A variation pool. WES analysis is a successful molecular diagnostic tool for rare genetic disorders, especially in those populations where the marriage of cousins is more frequent. Efficient and accurate genetic testing and counselling of the affected families are helpful for patient management and for reducing the disease burden in future generations. Abstract : Whole exome sequencing (WES) has been widely used in molecular diagnosis of single gene disorders. Patients in the present study had microcephaly, intellectual disability and nystagmus; however, the initial clinical diagnosis for Joubert syndrome (JBTS) was unclear. WES was perfromed for molecular diagnosis, which revealed a novel missense variant (c.4417C>G; p.Pro1473Ala) in CC2D2A, a gene previously known for JBTS9. The altered Ala1473 predicted a damaging effect on CC2D2A protein. The patients were re‐assessed and the JBST9 phenotype was confirmed.